Implementasi SAK ETAP dalam Penyajian Laporan Keuangan sesuai dengan PERMEN KUKM RI NO. 13/PER/M.KUKM/IX/2015 - Mahaitin H Sinaga; Wico Jontarudi Tarigan (Universitas Negeri Padang, 2021)
This study aims to analyze the implementation of SAK ETAP in the presentation of the cooperative's financial statements according to the Regulation of the Minister of KUKM RI No. 13/Per/M.KUKM/IX/2015 on the Cooperative of CU Bina Kasih P. Siantar. This study also aims to see the appearance of the financial statements presented by the CU Bina Kasih Cooperative P. Siantar. This study also aims to look at the presentation’s forms of financial statements presented by the Cooperative of CU Bina Kasih P. Siantar. The data collection technique in this study was by observing the technique of presenting financial statements at the Cooperative of CU Bina Kasih, then conducting interviews with the Cooperative Management, and obtaining documentation sourced from the Annual Financial Reports of the CU Bina Kasih Cooperative. The results of the study show that: (1) The Cooperative of CU Bina Kasih has not presented financial statements based on SAK ETAP according to the Minister of Finance of the Republic of Indonesia KUKM No. 13/Per/M.KUKM/IX/2015, (2) The components of the financial statements presented by the CU Bina Kasih P.Siantar Kopdit are only in the form of a Balance Sheet and Calculation of Remaining Operating Results and an Explanation of the Balance Sheet, and (3) Presentation of assets, liabilities, equity, income, and expenses by CU Bina Kasih Cooperative have not been presented based on their characteristics.